THE SOUNDNESSOF ARGUMENTSANDTHE EMERGENCE OF PARTICULAR FIGURES OF SPEECH IN MARIO TEGUH'S GOLDEN WAYS' SPEECH - Clemens Tjondropurnomo; Y. E. Budiyana; Heny Hartono (Soegijapranata Catholic University, 2011)
Motivation has evolved as a need of many people's life, today. The number of motivators also proliferates gradually along with their steadfast-buffs both at international and domestic scale. The man of the hour of Indonesian motivator currently is Mario Teguh. Persuasive language functions as a primary weapon to win over people. In this research, Toulmin's model (exposing the forms of argument structure) together with figures of speech are used to be the theories that correspond to central route and peripheral route in Elaboration Likelihood Model. The data which consist of three episodes of Mario Teguh Golden Ways were downloadedfrom Youtubewebsite, and transcribed for further analysis. The outcome of this research is that the arguments made by Mario Teguh shows the soundness of the arguments.In addition, some particular figures of speech often emergedin his speech. This article discusses the soundness of the argument, the forms of argument structure based on Tau/min's model and the discoveryoffigures of speech in Mario TeguhGo/denWays' speech.